Reframing reformulation: a theoretical-experimental approach: evidence from the Spanish discourse marker "o sea" - Salameh Jiménez, Shima (Sprache - Gesellschaft - Geschichte, 2021)
Reformulation studies offer a recent debate on reformulation and its semasiological-onomasiological treatment. Some researchers argue for a clear distinction between reformulation and other functions such as conclusion or correction; others defend the existence of different subtypes of reformulation based on such other functions, which are expressed by the same group of discourse markers in different languages. Both approaches are valid although their arguments and theoretical basis are opposed. The book presents an Eye-Tracking proposal to complement this debate experimentally. Results support an onomasiological approach to reformulation since experimental boundaries for each function (paraphrase, reformulation, conclusion and correction) have been detected